Identification of Leadership Effectiveness - Rani Tania Pratiwi; Deden Agustira; Dela Agustina (Yayasan Dekhalisha Global Prestise, 2025)
Leadership development is very fast, very influential on the condition of leadership itself. Where, every leader is required to be able to improve the quality of their leadership. Leadership is a process carried out by a leader in moving organizational members to be able to work together to achieve organizational goals effectively and efficiently. The quality of a person's process of leading greatly determines the effectiveness of his leadership in achieving the goals of the organization. An effective leader of course is when able to synergize the goals of individuals, groups and organizations. Leadership is not only limited to calculations and planning, doing checklists, even rational analysis, but leadership is also the ability to touch the hearts, feelings and emotions of members. The method used in this study is the Systematic Literature Review (SLR) method. The SLR method is used to identify, review, evaluate, and interpret all available research with topic areas of interest to phenomena, with specific relevant research questions. With the use of the SLR method, a systematic review and identification of journals can be carried out, which in each process follows the steps or protocols that have been set. The results showed that the dominant leadership style used in effective leadership is transformational leadership.